Osteocyte-specific dentin matrix protein 1: the role of mineralization regulation in low-magnitude high-frequency vibration enhanced osteoporotic fracture healing. Issue 7 (13th July 2022) - Li, Meng C. M.; Chow, Simon K-H.; Wong, Ronald M. Y.; Chen, Bailing; Cheng, Jack C. Y.; Qin, Ling; Cheung, Wing-Hoi
Abstract : Aims: There is an increasing concern of osteoporotic fractures in the ageing population. Low-magnitude high-frequency vibration (LMHFV) was shown to significantly enhance osteoporotic fracture healing through alteration of osteocyte lacuno-canalicular network (LCN). Dentin matrix protein 1 (DMP1) in osteocytes is known to be responsible for maintaining the LCN and mineralization. This study aimed to investigate the role of osteocyte-specific DMP1 during osteoporotic fracture healing augmented by LMHFV. Methods: A metaphyseal fracture was created in the distal femur of ovariectomy-induced osteoporotic Sprague Dawley rats. Rats were randomized to five different groups: 1) DMP1 knockdown (KD), 2) DMP1 KD + vibration (VT), 3) Scramble + VT, 4) VT, and 5) control (CT), where KD was performed by injection of short hairpin RNA (shRNA) into marrow cavity; vibration treatment was conducted at 35 Hz, 0.3 g; 20 minutes/day, five days/week). Assessments included radiography, micro-CT, dynamic histomorphometry and immunohistochemistry on DMP1, sclerostin, E11, and fibroblast growth factor 23 (FGF23). In vitro, murine long bone osteocyte-Y4 (MLO-Y4) osteocyte-like cells were randomized as in vivo groupings. DMP1 KD was performed by transfecting cells with shRNA plasmid. Assessments included immunocytochemistry on osteocyte-specific markers as above, and mineralized nodule staining. Results: Healing capacities in DMP1 KD groups were impaired. Results showed that DMP1 KD significantly abolished vibration-enhanced fracture healing at week 6. DMP1 KD significantly altered the expression of osteocyte-specific markers. The lower mineralization rate in DMP1 KD groups indicated that DMP1 knockdown was associated with poor fracture healing process. Conclusion: The blockage of DMP1 would impair healing outcomes and negate LMHFV-induced enhancement on fracture healing. These findings reveal the importance of DMP1 in response to the mechanical signal during osteoporotic fracture healing. Cite this article: Bone Joint Res  2022;11(7):465–476.